Prediction of low frequency sound fields in buildings near railway lines - Neves e Sousa, Albano (2012)
The design of new buildings in the vicinity of railway lines must consider protection against noise and vibrations induced by railway traffic. However, the prediction methods available involve heavy numerical models which have frequency limitations. In this paper a prediction method combining finite elements (FEM) with natural mode analysis is presented for use in reinforced concrete buildings with heavy walls. The method considers 2D FEM models of the railway, ground and buildings to identify the transfer function of vibration from the railway to building foundations. Also 3D models of the buildings are considered to identify the transfer functions of vibration from foundations to walls and floors. Finally, as the impedance of heavy walls and floors is much higher than the acoustic impedance of air, the numerically assessed vibration fields of walls and floors are used to calculate sound fields in rooms by means of natural mode analysis. A set of in situ measurements were made in two different situations in order to calibrate the prediction method and also to identify the factors which most affect vibration and sound transmission.